2013
DOI: 10.1186/1750-1172-8-196
|View full text |Cite
|
Sign up to set email alerts
|

Weekly oral alendronate in mevalonate kinase deficiency

Abstract: BackgroundMevalonate kinase deficiency (MKD) is caused by mutations in the MVK gene, encoding the second enzyme of mevalonate pathway, which results in subsequent shortage of downstream compounds, and starts in childhood with febrile attacks, skin, joint, and gastrointestinal symptoms, sometimes induced by vaccinations.MethodsFor a history of early-onset corticosteroid-induced reduction of bone mineral density in a 14-year-old boy with MKD, who also had presented three bone fractures, we administered weekly or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
(24 reference statements)
0
12
1
Order By: Relevance
“…To assess the effects of thiopurine treatment, some CD patients were recruited immediately prior to commencing AZA therapy, and longitudinal blood sampling was conducted over a followup period of 6 months. The analyses of Vδ2 T cell subset distribution in peripheral blood were conducted in a subgroup of pediatric CD patients (mean age, 13 years [range [7][8][9][10][11][12][13][14][15][16][17][18][19]; 50% male; CRP, mean 12.5 mg/l [range 5-39 mg/l]) and sex/age/ethnicity-matched IBS controls (mean age, 13 years [range [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; 50% male; CRP, <5 mg/l) in order to limit the effects of demography, historical pathogen exposure, and concomitant therapies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effects of thiopurine treatment, some CD patients were recruited immediately prior to commencing AZA therapy, and longitudinal blood sampling was conducted over a followup period of 6 months. The analyses of Vδ2 T cell subset distribution in peripheral blood were conducted in a subgroup of pediatric CD patients (mean age, 13 years [range [7][8][9][10][11][12][13][14][15][16][17][18][19]; 50% male; CRP, mean 12.5 mg/l [range 5-39 mg/l]) and sex/age/ethnicity-matched IBS controls (mean age, 13 years [range [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; 50% male; CRP, <5 mg/l) in order to limit the effects of demography, historical pathogen exposure, and concomitant therapies.…”
Section: Methodsmentioning
confidence: 99%
“…PAg are produced by a wide range of bacteria that can colonize the gut (1) and can also accumulate in host cells due to dysregulation of the mevalonate kinase metabolic pathway during malignant transformation or microbial infection (5,6). Intriguingly, human patients with mutations in the mevalonate kinase gene exhibit a severe neonatal colitis that can be successfully treated with bisphosphonate drugs, which modulate PAg synthesis and alter Vδ2 T cell function in vivo (7)(8)(9)(10). We recently reported that PAg exposure stimulates human blood Vδ2 T cells to upregulate the gut-homing integrin α4β7, and we identified Vδ2 T cells in human colonic biopsies that produced proinflammatory cytokines and enhanced IFNγ synthesis by intestinal CD4 + T cells (11).…”
Section: Introductionmentioning
confidence: 99%
“…However, a partial loss of efficacy in a TRAPS patient who received canakinumab has recently been described: surprisingly, when alendronate was added to canakinumab, in order to treat a concomitant corticosteroidinduced osteoporosis, disease activity was promptly and fully controlled [110]. These same findings were also strikingly described in a boy with mevalonate kinase deficiency syndrome, a metabolic disorder included in the family of AIDs [111].…”
Section: Traps Treatmentmentioning
confidence: 78%
“…There is an anecdotal report of disease resolution with oral alendronate, which was initially prescribed to treat osteoporosis in a 14-year-old boy with HIDS [8]. Bisphosphonates inhibit the already compromised MVK pathway [38] and are, therefore, considered as contraindicated in HIDS.…”
Section: Treatmentmentioning
confidence: 99%